Efektivitas Pendidikan Kesehatan melalui Media Permainan Ludo terhadap Peningkatan Pengetahuan, Sikap, dan Perilaku Siswa Sekolah Dasar dalam Pencegahan Adiksi Video Game - Ana Puspita Indah; Indria Laksmi Gamayanti; Rendra Widyatama (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Effectiveness of video game addiction prevention using ludo game for elementary school studentsPurposeThis study aimed to determine the effectiveness of ‘Ludo game’ for increasing knowledge, attitudes, and behaviors of elementary school students concerning video-game addiction.MethodsThe research was a quasi-experimental study with pre and post tests and a control group design. The subjects were 99 elementary school students who were divided into treatment groups (two groups of intervention) and a control group. The data were collected using a questionnaire of knowledge, attitudes and behavior. Data analysis used paired t-test and analysis of variance (ANOVA) with significance level of 95% (p <0.05). ResultsThe characteristics of the study subjects in all three groups before the intervention were normally distributed. Paired t-test results showed that the ludo game and interactive lectures can improve knowledge, attitudes, and behaviors. However, there was no significant difference of knowledge, attitudes, and behaviors through Ludo compared to health education through interactive lectures in health education delivery. ConclusionLudo game and interactive lectures together can effectively improve the knowledge, attitudes, and behavior of elementary school students. Health education through ludo games was no more effective than the interactive lecture methods in increasing the knowledge, attitudes, and behavior of students on the prevention of video-game addictions.